Peningkatan Higiene Sanitasi pada Proses Pengolahan Sajian Kuliner pada Kelompok Tani Mandiri - Riani, Ira Gusti; Handayani, Marta Tika; Ritonga, Nia Boru (Penerbit Goodwood, 2023)
Purpose: The hygiene and sanitation training activities that have been carried out aime to educate Mandiri’s Farmers .Group so they know about hygiene and sanitation concepts and hygiene and sanitation applications, especially for culinary service processing, and minimize foodborne diseases. Methodology: The service is carried out by providing assistance to members of Mandiri’s Farmer Group. The method of community service activities is carried out by delivering material using the lecture method related to hygiene and sanitation in the processing of culinary products, as well as direct questions and answers or discussions regarding hygiene and sanitation in the processing of culinary products. Results: The training provided to improve knowledge, especially for Mandiri’s Farmer Group in Palembang City. The material presented was related to the introduction of hygiene and sanitation when processing culinary offerings, the importance of maintaining hygiene and sanitation in culinary offerings, and several types of diseases that can be contracted as a result of not maintaining hygiene and sanitation during the processing process.